Rock glaciers and natural dams in Central Asia - Rosenwinkel, Swenja (2018)
The formation and breaching of natural dammed lakes have formed the landscapes, especially in seismically active high-mountain regions. Dammed lakes pose both, potential water resources, and hazard in case of dam breaching. Central Asia has mostly arid and semi-arid climates. Rock glaciers already store more water than ice-glaciers in some semi-arid regions of the world, but their distribution and advance mechanisms are still under debate in recent research. Their impact on the water availability in Central Asia will likely increase as temperatures rise and glaciers diminish. This thesis provides insight to the relative age distribution of selected Kyrgyz and Kazakh rock glaciers and their single lobes derived from lichenometric dating. The size of roughly 8000 different lichen specimens was used to approximate an exposure age of the underlying debris surface. We showed that rock-glacier movement differs signifcantly on small scales. This has several implications for climatic inferences from rock glaciers. First, reactivation of their lobes does not necessarily point to climatic changes, or at least at out-of-equilibrium conditions. Second, the elevations of rock-glacier toes can no longer be considered as general indicators of the limit of sporadic mountain permafrost as they have been used traditionally. In the mountainous and seismically active region of Central Asia, natural dams, besides rock glaciers, also play a key role in controlling water and sediment infux into river valleys. However, rock glaciers advancing into valleys seem to be capable of infuencing the stream network, to dam rivers, or to impound lakes. This influence has not previously been addressed. We quantitatively explored these controls using a new inventory of 1300 Central Asian rock glaciers. Elevation, potential incoming solar radiation, and the size of rock glaciers and their feeder basins played key roles in predicting dam appearance. Bayesian techniques were used to credibly distinguish between lichen sizes on rock glaciers and their ...